Measurements of Texture of Soils Formed from Glaciolimnic Sediments by Areometric Method, Pipette Method and Laser Diffraction Method - Orzechowski Mirosław; Smó;lczyński Sławomir; Długosz Jacek; Pozniak Paweł (Soil Science Annual, 2014)
The aim of the research was to compare the results of texture analyses of glaciolimnic sediments deposited in the basins of ice-dammed lakes origin in north eastern Poland. The study was carried out using aerometric method, pipette method and laser diffraction method. The studied soils were classified as Haplic and Mollic Vertisol, Vertic Cambisol, and Gleyic Chernozem. The soils were formed from clayey (clay, heavy clay), loamy (loam, clay loam, sand clay loam) and silty (silt loam, clay loam) deposits. The studied soils did not contain fractions > 2.0 mm. The amounts of clay fraction (< 0.002 mm) measured by areometric and pipette methods were similar and strongly correlated. In comparison to laser diffraction method, these amounts were 3-4-fold higher. The sub-fraction of fine silt (0.02-0.002 mm) predominated in soil formations analyzed by laser diffraction method. In comparison to areometric or pipette method, the amounts of fine silt were 2-4 fold higher. Basing on the calculated sedimentological indices, it was stated that the examined soils were well sorted and the mean grain diameter (GSS) was very low and did not exceed 0.005 mm in areometric and pipette methods, and 0.011 mm in laser diffraction method for clay sediments.